1999
DOI: 10.1088/0957-4484/10/3/310
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and experiments on friction and wear of diamond: a material for MEMS and NEMS application

Abstract: Abstract.To date most of the microelectromechanical system (MEMS) devices have been based on silicon. This is due to the technological know-how accumulated on the manipulation, machining and manufacturing of silicon. However, only very few devices involve moving parts. This is because of the rapid wear arising from high friction in these silicon-based systems. Recent tribometric experiments carried out by Gardos on silicon and polycrystalline diamond (PCD) show that this rapid wear is caused by a variety of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…49 The atomic interaction between the atoms of the tool and the workpiece could be better understood from the simulation results. Cagin et al (1999) investigated the nano-frictional characteristics for two flat diamond specimens sliding under contact. The results showed that the friction coefficient value was in the range of 0.01 to 0.25 and the value changed with respect to sliding direction.…”
Section: Numerical Analysismentioning
confidence: 99%
“…49 The atomic interaction between the atoms of the tool and the workpiece could be better understood from the simulation results. Cagin et al (1999) investigated the nano-frictional characteristics for two flat diamond specimens sliding under contact. The results showed that the friction coefficient value was in the range of 0.01 to 0.25 and the value changed with respect to sliding direction.…”
Section: Numerical Analysismentioning
confidence: 99%
“…They found that larger loads also led to slip motion and plastic deformation of the tip. Other atomistic simulation work can be found in [11][12][13] and ex-perimental work in Refs. [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Other atomistic simulation work can be found in [11][12][13] and ex-perimental work in Refs. [13][14][15]. Most MD studies of the stick-slip have been concerned with sliding friction [10,11,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52] This method is specifically developed for studying tribological properties of materials.…”
Section: Nonequilibrium MDmentioning
confidence: 99%